Survey of Ethiopian sheep and goat types. 1. Southern Ethiopia - Tolera, Adugna (Awassa College of Agriculture, 1996)
A survey was conducted in Kochre (Fiseha Genet) Woreda (district) of Gedeo Zone, southern Ethiopia to identify the production situation and some productivity and physical characteristics of sheep and goats traditionally managed by small farmers in the area. The adult male: female ratio is 1: 4.2 and 1: 3.7 for sheep and goats, respectively. The sheep have thin to semi-fat and long tail. The age at first parturition (21 months for sheep and 19.5 months for goats) and the parturition intervals (11.7 and 10.8 months for sheep and goats, respectively) are comparable to reported values in the literature for other African sheep and goats under traditional management. Disease and parasite infestation and inadequate feed supply during the dry season are major constraints affecting small ruminant productivity in the area. Dependence on breeding males borrowed from neighbours (50% of the respondents) could also hamper the reproductive performance of the flocks. Thus, extension work aimed at improving feed supply during dry season, control of disease and parasite and selection and proportionate distribution of breeding males are viable options for improving small ruminant productivity in the area.